DINAMIKA SPASIAL PENGGUNAAN LAHAN PERTANIAN BERDASARKAN CITRA PENGINDERAAN JAUH Tinjauan Dalam Rangka Menuju Pertanian Lestari di Daerah Aliran Sungai (DAS) Noongan dan Panasen Kabupaten Minahasa Provinsi Sulawesi Utara - , Joudie N Luntungan, Ir.,M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Spatial Dynamics of Agricultural Land Use based on Remote Sensing Imagery, an evaluation towards the Sustainable Agriculture in Noongan and Panasen watershed in Minahasa Regency, Province of North Sulawesi aims to: (1) assess the accuracy of land parameters that can be extracted from remote sensing imagery, which is used in preparation of Spatial Dynamics Model of Agricultural Land Use